An investigation into the complex formation of membrane bound cytochrome b5 isolated from ovine liver microsomes - Adriaanse, Craig Vernon (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)-- Stellenbosch University, 2013.